Set pair analysis for risk assessment of water inrush in karst tunnels - Wang, Yingchao; Jing, Hongwen; Yu, Liyuan; Su, Haijian; Luo, Ning (Bulletin of engineering geology and the environment, 2017)
Considering the uncertain characteristics of water inrush in karst tunnels, the set pair analysis (SPA) method was newly applied in this study for risk assessment of water inrush. First, karst hydrology and engineering geological conditions were considered, and several main influencing factors were selected as evaluation indices, such as formation lithology, unfavorable geology, groundwater level and contact zone of dissolvable as well as other factors. Second, a set pair was established with the combination of the evaluation indices and the standards of risk grade. Then, the evaluation indices of water inrush were divided into two main types: economic and cost indices. Based on set pair analysis (SPA), the graded connection degrees of evaluation indices were calculated. Finally, the established risk evaluation model of water inrush with set pair analysis was applied to the Jigongling tunnel on the line of the Fanba expressway in China. The results not only are consistent with the results of the attribute mathematical theory, but also agree well with practical situations. In addition, the method of set pair analysis used in this study could provide relatively high accuracy when applied to risk assessment of water inrush in karst tunnels. Meanwhile, SPA is simple, feasible and easy to implement. The presented method has been validated as an effective method of risk assessment for water inrush, which also has good prospects for further engineering applications.